Anacardato de cálcio como promotor de crescimento alternativo para leitões na fase de creche - Matos, Amanda Veruska Silva de (2015)
The objective was to evaluate the calcium anacardate as an alternative growth promoter in feed for piglets at nursery phase, on performance, occurrence of diarrhea, serum parameters, intestinal morphology and pH of the gastrointestinal contents. A total of 60 piglets were used, weaned at 21 days of age, distributed among 5 treatments: negative control (CN) - feed without growth promoter inclusion; positive control (CP) - feed with antibiotic growth promoter (AGP); AC 0.4% - feed with 0.4% calcium anacardate; AC 0.8% - feed with 0.8% calcium anacardate; AC 1.2% - feed with 1.2% calcium anacardate, with 6 replicates per treatment, considering the pen containing 2 piglets as experimental unit. The experiment lasted 22 days, divided in period I (21-32 days) and period II (21-42 days). It was observed that the performance of piglets fed with calcium anacardate didn’t differ from those fed with AGP. The inclusion of calcium anacardate from 0.8% in the feed resulted in serum globulin levels similar to those animals receiving the feed with AGP. Although the occurrence of diarrhea was lower in animals that received AGP, the villus height (VH) and villus height-to-crypt depth ratio (V/C) in the animals who received calcium anacardate in the diet was similar to the treatment with AGP. Calcium anacardate can act as a replacement for AGP in diets for piglets at nursery phase, considering that from the inclusion of 0.8% showed benefits in intestinal morphology and serum parameters of animals.